Corn Yield and Foliar Diagnosis Affected by Nitrogen Fertilization and Inoculation with Azospirillum brasilense - Galindo, Fernando Shintate [UNESP]; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP]; Buzetti, Salatier [UNESP]; Kondo Santini, Jose Mateus [UNESP]; Alves, Cleiton Jose [UNESP]; Nogueira, Lais Meneghini [UNESP]; Ziolkowski Ludkiewicz, Mariana Gaioto [UNESP]; Andreotti, Marcelo [UNESP]; Miranda Bellotte, Joao Leonardo [UNESP] (Soc Brasileira De Ciencia Do Solo, 2016)
The biological nitrogen fixation (BNF) process in grasses is caused by diazotrophic bacteria, particularly Azospirillum brasilense. However, studies are lacking on BNF efficiency to define how much mineral nitrogen (N) can be applied to achieve more sustainable high yields. Furthermore, there should be an analysis of whether urea with the urease enzyme inhibitor NBPT is less harmful, benefiting BNF in grasses. The objective of this study was to evaluate the effect of N sources and N rates associated with inoculation with Azospirillum brasilense regarding foliar diagnosis and leaf chlorophyll index (LCI), agronomic efficiency (AE), and corn grain yield in the Cerrado (Brazilian tropical savanna) region. The experiment was conducted in a no-tillage system in a Latossolo Vermelho Distroferrico (Oxisol). A randomized block experimental design was used with four replications in a 2 x 5 x 2 factorial arrangement as follows: two N sources - urea and Super N, urea with urease enzyme inhibitor NBPT [N - (n-butyl thiophosphoric triamide)]; five N rates (0, 50, 100, 150, and 200 kg ha(-1)) applied in topdressing; and two seed inoculation treatments, one with and one without A. brasilense. N rate positively influenced the LCI and concentrations of N, S, and Mn in leaves, and may increase the concentrations of P, Cu, and Fe; however, higher N rates can reduce AE. The N sources had similar effects, and therefore urea is recommended for N fertilization. Inoculation with A. brasilense decreased leaf concentration of Fe and increased LCI, leaf concentration of P, AE, and corn grain yield; the use of this diazotrophic bacterium is therefore viable even when high rates of N are applied.
Keywords: Zea mays L.; urease inhibitor; nitrogen rates; BNF; no-tillage system